Policies of 'modernisation' in European education: Enactments and consequences. (November 2015) - Rasmussen, Palle; Larson, Anne; Rönnberg, Linda; Tsatsaroni, Anna
The five articles in this special issue offer empirically and theoretically informed accounts from education policy research carried out in different national contexts in Europe. This special issue sheds light on how modernising approaches to educational governance and reform, grouped under the umbrella of new public management, are strongly present in European education policy, both at transnational levels and in individual countries, and points to important implications for these developments.